Analysis of Skin Protection from the Dangers of Sun Exposure Using Color Variations and Types of Cotton Fabrics - Norliani Norliani; Mislan Mislan; Pratiwi Sri Wardani; Erlinda Ratnasari Putri (Lambung Mangkurat University Press, 2023)
Cotton fabric is a comfortable clothing material to wear in tropical climates. In addition to the comfort aspect, cotton cloth is expected to be able to protect the skin from the dangers of sun exposure. This research was conducted with the aim of knowing the optimum amount of protection produced by cotton cloth, determining the type and color of cotton cloth that is most effectively used as a protector, and knowing the SPF (sun protection factor) value category based on the type and color of cotton cloth. This study used three types of cotton cloth, each consisting of four colors, as well as a Digital Environment Multimeter which was used to measure the intensity of sunlight in units of lux. The protection value is obtained by comparing the intensity of sunlight without a cotton cloth protector (lux) with the intensity of sunlight using a cotton cloth protector (lux). The results obtained show that the most optimum protection value is found in black toyobo cotton cloth with an SPF value of 54.4 and a transmittance of 1.8%. The cotton fabrics that provided the most effective protection based on type and color were black and blue toyobo, medina and Japanese cotton fabrics. Based on the SPF value obtained, it can be seen that black and blue toyobo cotton fabrics, and black madinah cotton fabrics have a very good protection category. The black and blue Japanese cotton fabrics, as well as the blue medina type, have a good protection category, while the orange Toyobo cotton fabrics have a sufficient protection category.